Hubungan dan impak mekanisma tadbir urus korporat terhadap prestasi syarikat - Noorul Farha Mohd Jumali (Tanjong Malim, 2016)
Hubungan dan impak mekanisma tadbir urus korporat terhadap prestasi syarikat by Noorul Farha Mohd Jumali